Clinicopathological study of 50 cases of Dengue - Vaibhav Mane; Sushant Mohite (International Journal of Medical Research and Review, 2015)
Aim and objective: The objective of this study was to correlate laboratory tests during the evolution of dengue fever, comparing frequencies between the different clinical forms in order to use test results to predict the severity of the disease.Methods: This is an observational, descriptive and retrospective study of 50 patients with clinical and serological diagnoses of dengue fever. The tests analyzed were blood count, platelet count, and serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) concentrations.Results: Thrombocytopenia and elevated transaminases were observed in patients with classic dengue fever. The main laboratory abnormalities found in dengue hemorrhagic fever were thrombocytopenia, hemoconcentration and elevated transaminases, similar to severe dengue with the exception of hemoconcentration. Most laboratory abnormalities started on the 3rd day but were more evident on the 5th day with restoration of values by the 11th day; this was more prominent in under 15-year-olds and with the more severe clinical forms.Conclusion: These results are relevant in assessing the disease because they can be used as markers for more severe forms and can help by enabling the adaptation of the therapeutic conduct to the needs of individual patients.